Survival Analysis and Its Predictors Among Hemodialysis Patients at Saint Paul Hospital Millennium Medical College and Myungsung Christian Medical Center in Addis Ababa, Ethiopia, 2021 - Betiru EA; Mamo E; Jara Boneya D; Adem A; Abebaw D (International Journal of Nephrology and Renovascular Disease, 2023)
Eyob Assefa Betiru,1 Ephrem Mamo,2 Dube Jara Boneya,3 Abebawork Adem,4 Dessie Abebaw5 1General Public Health Department, Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia; 2Public Health Departments, Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia; 3Departments of Public Health College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 4Departments of Public Health College of Health Sciences, Gambi Medical College, Addis Ababa, Ethiopia; 5Public Health Department of Reproductive Health’s, Yekatit 12 Hospital Medical College, Addis Ababa, EthiopiaCorrespondence: Eyob Assefa Betiru, Email eyoba116@gmail.comBackground: Diabetes mellitus and hypertension are the most prominent conditions causing chronic kidney disease and eventually end-stage renal disease. Renal replacement therapy, particularly hemodialysis (HD), is the mainstay of treatment. The aim of this study is to assess the overall survival status of HD patients and potential survival predictors at Saint Paul hospital millennium medical college (SPHMMC) and Myungsung Christian Medical Center (MCM) in Addis Ababa, Ethiopia.Methods: A retrospective cohort study was conducted on HD patients at SPHMMC and MCM general hospital from January 1, 2013 to December 30, 2020. Kaplan Meier, Log-rank, and Cox proportional regression models were used for the analysis. Estimated risks were reported as hazard ratios with 95% confidence intervals and P< 0.05 was considered as having a significant association.Results: A total of 128 patients were included in the study. Median survival time was 65 months. The predominant co-morbid condition was found to be diabetes mellitus with hypertension (42%). The total risk time for these patients was 143,617 person years. The overall incidence rate of death was 2.9 per 10,000 person years (95% CI=2.2– 4). Patients who developed blood stream infection were 2.98-times more likely to die than those without infection. Those using an arteriovenous fistula were 66% less likely to die than those using a central venous catheter. Additionally, patients treated in a government-owned facility were 79% less likely to die.Conclusion: The study identified that the median survival time of 65 months was comparable with developed nations. Significant predictors of death were found to be blood stream infection and type of vascular access. Government-owned treatment facilities showed better patient survival.Keywords: survival status, survival predictors, hemodialysis predictors